KONSTRUKSI DAN REPRODUKSI SIMBOLIK TRADISI JAWA DALAM PERTUNJUKAN TEATER REMAJA DI KOTA SOLO - Ansari, Isa (Acintya, 2014)
This research aims to identify and describe how the adult’s theater groups express java tradition intheir art performances, specifically when local government is focusing on revitalizing the tradition.To reach the main purpose, researcher uses cultural reproduction perspective which develops aroundsociologist and anthropologist. In data analyzing, the researcher tries to combine the cultural reproductionand dramaturgy theories in theater. Therefore the analyzing process is done by dividing structureand texture. The research result shows that there are two important points done by the adult’stheater groups. First is negotiating the performance form in the artistic and value. Second is transformingthe aesthetic of performance.Keywords: construction, reproduction, Java tradition